Manajemen Pendidikan Karakter Melalui Perspektif Islam dalam Meningkatkan Disiplin Peserta Didik - Bisri Mustofa; Novi Rukhviyanti; Ujang Cepi Barlian (Jurnal Syntax Transformation, 2022)
The purpose of this study is to find out the root of character education problems to improve the discipline of learners. The application of this discipline is an unsolved problem in line with the complexity of environmental change, both on the planning, implementation and assessment side. Complexity of change leads to conflicts of interest, disorientation of values and functions, and the onset of conflict. Complexity arises along with changes that give birth to wild and uncontrollable behavior causing further weakening and loss of values of truth, honesty, a sense of justice, humanity and civility. There are a few things that make this problem. Among them is not optimal empowerment of raw input learners, empowerment of instrumental inputs including curriculum, not optimal involvement of environmental input and output of character education. This research focuses on issues related to planning, implementation, and assessment issues in management of character education through an Islamic perspective in enhancing the discipline of learners in SMAN 10 bandung. The usefulness of this research first aims to obtain an overview of character education management through Islamic persupancy in improving discipline. In addition, the second is to know and analyze the planning of character education management through an Islamic perspective in improving discipline. Based on the results of SMAN 10 Bandung research in general, it can be concluded that character education management to improve student discipline has been carried out with the running of planning, implementation and assessment functions. Character education planning is outlined in the vision and mission and goals of the school which is then poured in the preparation of learning which basically each subject contains materials related to character. Assessment and evaluation activities are carried out during the learning process and at the end of the learning